ANTHROPOGENIC INFLUENCE ON RELIEF OF ARMENIA AND SECONDARY TECHNOGENIC PROCESSES (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
Alterations of the relief of the territory of Armenia in the process of economic activity of man and forming of secondary technogenic processes, directed to reconstruct the balance of former condition of the relief broken by man, are examined in the article. It is noted that anthropogenic influence on the relief acquires greater scale year by year. It is necessary to give competent forecast of expected secondary processes for professional planning of transformation of existing relief for preventing undesirable consequences.
Keywords: Armenia; relief; secondary anthropogenic processes